Anti-MDA5 Antibody Linking COVID-19, Type I Interferon, and Autoimmunity: A Case Report and Systematic Literature Review - Tonutti, Antonio; Motta, Francesca; Ceribelli, Angela; Isailovic, Natasa; Selmi, Carlo; De Santis, Maria (Frontiers in Immunology, 2022)
Introduction. The SARS-CoV-2 infection has been advocated as an environmental trigger for autoimmune diseases, and a paradigmatic example comes from similarities between COVID-19 and the myositis-spectrum disease associated with antibodies against the melanoma differentiation antigen 5 (MDA5) in terms of clinical features, lung involvement, and immune mechanisms, particularly type I interferons (IFN). Case report. We report the first case of anti-MDA5 syndrome with skin manifestations, constitutional symptoms, and cardiomyopathy following a proven SARS-CoV-2 infection. Systematic literature review. We systematically searched for publications on inflammatory myositis associated with COVID-19. We describe the main clinical, immunological, and demographic features, focusing our attention on the anti-MDA5 syndrome. Discussion. MDA5 is a pattern recognition receptor essential in the immune response against viruses and this may contribute to explain the production of anti-MDA5 antibodies in some SARS-CoV-2 infected patients. The activation of MDA5 induces the synthesis of type I IFN with an antiviral role, inversely correlated with COVID-19 severity. Conversely, elevated type I IFN levels correlate with disease activity in anti-MDA5 syndrome. Based on the available evidence, we hypothesize that the strong type I IFN response observed in patients with anti-MDA5 syndrome, might harbor protective effects against viral infections, including COVID-19.